PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN PENDEKATAN PBL DI KELAS IV SD - Monica, Cynthia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Background of this research is social science learning still use teacher sentre, consequently, the students did not involve actively the learning process. This research aimed to describle the improving the student achievement in social science learning by using Problem Based Learning (PBL) at grade IV SD Negeri 04 Bukit Apit Puhun Kota Bukittinggi. Kind of this resears was action research with quantitative and qualitative approach. The result of this research showed that, the student achievement in cycle I was 74% and this increased to 85% in cycle II. From the result it can be concluded that Problrm Based Learning (PBL) approach and increase the student learning achievement in social science learning at gradeIV SD Negeri 04 Bukit Apit Puhun Kota Bukittinggi.